Insights into Recent Techniques for Improving Shelf Life and Value Addition in Pearl Millet Flour: A Mini Review on Recent Advances: Value addition in pearl millet - Goswami, Suneha; T, Vinutha; Kumar, Ranjeet Ranjan; Singh, Tejveer; Ali, Ansheef; Meena, Mahesh Chand; Singh, Sumer Pal; Dulait, Keshram; Satyavathi, C Tara (Annals of Arid Zone, 2023)
Pearl millet is a climate resilient crop, which is nutritionally rich and has numerous health benefits. Despite its nutritional significance, pearl millet is not popular among the consumers and food industries due to poor shelf life and dough quality. To address these problems, researchers have studied various processing technologies like heat treatments (hydrothermal, near infrared rays, microwave, ohmic heating etc.), decortication, malting, germination and fermentation to enhance the shelf life of pearl millet flour. Studies on improving pearl millet dough quality were also reported, wherein vital wheat gluten was reconstituted in pearl millet flour for better dough quality. All these methods and technologies are discussed in this review. So by adopting these technologies, pearl millet can replace wheat as a sustainable ingredient in many baked and prepared preparations and become a new staple food with better nutrition and health.